Social protection for agriculture and resilience: Highlights, lessons learned, and priorities for One CGIAR - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2021)
How do social protection programs influence agricultural growth and nutrition, and what are the implications of this for program design? PIM research on the impact of social protection programs and complementary interventions for agricultural growth and nutrition made significant contributions to research and policy, including through impact evaluations of national food and cash transfer programs (e.g., the Takaful and Karama Program in Egypt, the Productive Safety Net Program in Ethiopia, and the Programme de Filets Sociaux “Jigisemejiri” in Mali), pilot studies (in Bangladesh, Ethiopia, Ghana, India, Indonesia, Malawi, Mali, Nigeria, Pakistan, Senegal, Tanzania, and Yemen), and papers and review studies covering many low- and middle-income countries. Social protection programs that provide cash or in-kind transfers alone often show limited short-term effects on agriculture or nutrition outcomes, although there is evidence of impacts of cash transfers alone on child nutrition in cases of extreme deprivation or when transfers are very large. The flagship’s research shows that social protection programs that bundle cash or in-kind transfers with high-quality complementary programming can generate large, significant improvements in agriculture and nutrition outcomes. Such complementary programming includes agricultural extension and nutrition behavior change communication (BCC).